Applying ethology to design human-oriented technology. Experimental study on the signalling role of the labelling effect in technology’s empowerment - Modliński, Artur; Gladden, Matthew (Human Technology, 2021)
We transpose ethological and sociological theory on autonomous technology management using two signals: country of origin and security certificate status. Our research shows that to understand the degree of attractiveness of human-oriented technology that has been techno-empowered, we should analyze the natural interspecies interaction taking place in the ecological niche. A 2×4 between-subject experiment on a fictitious brand was designed to test three hypotheses regarding autonomous office assistant empowerment. Two hundred ninety-five people (54% females) participated in the study. We found that people have a higher intention to use autonomous office assistants if their country of origin is unknown but a security certificate is provided. Gender moderates the ‘label effect’ so that females have a higher intention to allow autonomous office assistant to make independent decisions if they do not know the country of origin but a safety certificate is provided, whereas for males, neither of these labels influences such intention significantly.